2020
DOI: 10.1039/d0ra02723e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PVDF/FMBO composite electrospun nanofiber for effective arsenate removal from water

Abstract: In this study, novel electrospun nanofibers composed of organic polyvinylidine fluoride and inorganic Fe–Mn binary oxide nanoparticles were fabricated using an electrospinning technique for adsorptive removal of As(v) from polluted water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Apart from the PVDF coating, electrospinning of PVDF, and its copolymers and composites with different nanomaterials can be performed to utilize advantages of both materials. These composites are mostly used in energy harvesting and environmental remediation applications [ 41 , 42 , 43 , 44 ]. In recent times, only a limited number of reports have been published on their applications in the biomedical field.…”
Section: Biopolymer Coatings For Surface Modificationmentioning
confidence: 99%
“…Apart from the PVDF coating, electrospinning of PVDF, and its copolymers and composites with different nanomaterials can be performed to utilize advantages of both materials. These composites are mostly used in energy harvesting and environmental remediation applications [ 41 , 42 , 43 , 44 ]. In recent times, only a limited number of reports have been published on their applications in the biomedical field.…”
Section: Biopolymer Coatings For Surface Modificationmentioning
confidence: 99%
“…The characteristic peak at 720 cm À1 is assigned to the Ti-O band, 54 the blue shift of the peaks from 720 to 691 cm À1 reveals interactions between TiO 2 and As(III), indicating the formation of the Ti-O-As bond. 55 In addition, Parisa et al 56 observed a new peak at 580 cm À1 after the adsorption of As(V) by a novel Fe-Mn binary oxide nanoparticle, indicating the presence of Fe-O-As vibrations. Likewise, we believe that the broad peak (in the dotted box) formed after the addition of As(III) shown in Fig.…”
Section: Characterizations Of Tio 2 and As(iii)/tiomentioning
confidence: 99%
“…Utilizing the synergistic effect of the oxidation of manganese dioxide and strong adsorption of iron oxides to As 5+ , Aliahmadipoor et al developed a novel electrospun nanohybrid membrane incorporating inorganic Fe-Mn binary oxide nanoparticles into PVDF for the decontamination of As 5+ . A maximum As 5+ uptake capacity of around 21.32 mg/g has been attained by the membrane and 70% of the initial adsorption capacity has been regenerated by a diluted alkaline solution [64].…”
Section: Removal Of Major Water Pollutantsmentioning
confidence: 99%